circGprc5a Promoted Bladder Oncogenesis and Metastasis through Gprc5a-Targeting Peptide - Chaohui Gu; Naichun Zhou; Zhiyu Wang; Guanru Li; Yipping Kou; Shunli Yu; Yongjie Feng; Long Chen; Jinjian Yang; Fengyan Tian (Elsevier, 2018)
Bladder cancer is a serious cancer in the world, especially in advanced countries. Bladder cancer stem cells (CSCs) drive bladder tumorigenesis and metastasis. Circular RNAs (circRNAs) are involved in many biological processes, but their roles in bladder oncogenesis and bladder CSCs are unclear. Here, we identified that circGprc5a is upregulated in bladder tumors and CSCs. circGpr5a knockdown impairs the self-renewal and metastasis of bladder CSCs, and its overexpression exerts an opposite role. circGpr5a has peptide-coding potential and functions through a peptide-dependent manner. circGprc5a-peptide binds to Gprc5a, a surface protein highly expressed in bladder CSCs. Gprc5a knockout inhibits the bladder CSC self-renewal and metastasis. circGprc5a-peptide-Gprc5a can be utilized to target bladder cancer and bladder CSCs. Keywords: bladder cancer, cancer stem cells, Gprc5a, peptide